IMPLEMENTASI APE PUPPET THEATER DALAM MENSTIMULASI BAHASA ANAK USIA 3-4 TAHUN - Iklimatul Hasanah; RR. Deni Widjayatri (Jurnal Caksana : Pendidikan Anak Usia Dini, 2024)
Limited vocabulary can affect aspects of a child's language. The understanding of children aged 3-4 years reaches 900 words. The aim of the research is to determine the implementation of APE puppet theater in stimulating language aspects of children aged 3-4 years. The subjects in the research were children aged 3-4 years at TKIT Villa Madani TK-A with a total of 18 children, 9 boys and 9 girls. In this research, the method used is descriptive qualitative. The research uses data collection techniques through observation and documentation. The results obtained in the research describe the implementation of the APE puppet theater at TKIT Villa Madani, TK-A class, in the initial conditions, the language aspects of children aged 3-4 years were in good condition. After the children were given the APE puppet theater, the indicator of ability to understand language was rated quite well, there were 10 children, 6 children with a fairly good rating, 2 children with a very good rating. Meanwhile, the indicator for expressing language received a poor assessment by 1 child, a fairly good assessment was achieved by 9 children and a good assessment was achieved by 8 children. It can be concluded that (a) educational puppet theater games can stimulate the language aspects of children aged 3-4 years with good assessments. (b) the form of strategy used in educational puppet theater games is storytelling. (c) Puppet theater games can train language understanding and language expression in children aged 3-4 years. (d) gender can influence language stimulation in children aged 3-4 years. (e) the existing understanding of children aged 3-4 years can increase by approximately 500 understandings according to the stories played in the APE puppet theater. (e) during the learning process using the APE puppet theater, the children looked enthusiastic.